Homo‐Nuclear Hetero‐Atomic Conjugated Reticular Oligomers for Heterojunction: A Novel “Electron Medium” for Panel Photoelectrocatalysis - Ruijuan Zhang; Boying Zhang; Haining Liu; Linda Jewell; Xinying Liu; Shanlin Qiao (Advanced Science)
Abstract A substantial challenge in employing covalent organic frameworks (COFs) for photoelectrochemical (PEC) water splitting lies in improving their solution‐processability while concurrently facilitating the transfer of charges and mass to the catalytic sites. Herein, we synthesize a solution‐processable conjugated reticular oligomers (CROs), and further embed ruthenium (Ru) into the CRO, forming a CRO‐Ru with homo‐nuclear hetero‐atomic. Thereafter, CRO and CRO‐Ru construct an organic–organic heterojunction membrane at the nanoscale. This design achieves perfect lattice matching, significantly reducing the energy barrier of mass transfer, and effectively lowering the recombination rate of charge carriers. The optimized photocathode, CuI/CRO‐Bpy:CRO‐Bpy‐Ru‐1:1+P3HT/SnO2/Pt, exhibits an efficiency of 111.0 µA cm−2 at 0.4 V versus a reversible hydrogen electrode (RHE). Compared with the original bulk COFs and CROs, the efficiency is significantly improved. The apparent improvements in charge carrier separation and transfer are responsible for the high PEC activity. In the heterojunction, the incorporation of CRO‐Bpy‐Ru with a longer excited‐state lifetime and a substantial built‐in electric field has effectively accelerated the photo‐induced electron transfer from the conduction band (CB) of CRO‐Bpy to the valence band (VB) of CRO‐Bpy‐Ru, effectively suppressing the recombination of charges. These findings offer significant guidance for the design and optimization of high‐performance photoelectrochemical catalysts.